Characterization of Three Calcium-Dependent Protein Kinases of Cryptosporidium parvum - Zhang, Qiang; Shao, Qian; Guo, Yaqiong; Li, Na; Li, Yu; Su, Jiayuan; Xu, Rui; Zhang, Ziding; Xiao, Lihua; Feng, Yaoyu (Frontiers in Microbiology, 2021)
In Cryptosporidium spp., calcium-dependent protein kinases (CDPKs) are considered promising targets for the development of pharmaceutical interventions. Whole-genome sequencing has revealed the presence of 11 CDPKs in Cryptosporidium parvum (CpCDPKs). In this study, we expressed recombinant CpCDPK4, CpCDPK5, and CpCDPK6 in Escherichia coli. The biological characteristics and functions of these CpCDPKs were examined by using quantitative reverse transcription PCR (qRT-PCR), immunofluorescence microscopy, and an in vitro neutralization assay. The expression of the CpCDPK4 gene peaked at 12 h post-infection, the CpCDPK5 gene peaked at 12 and 48 h, and the CpCDPK6 gene peaked at 2–6 h. CpCDPK4 protein was located in the anterior and mid-anterior regions of sporozoites, and CpCDPK5 protein was located over the entire sporozoites, while CpCDPK6 protein was expressed in a spotty pattern. Immune sera of CpCDPK4 and CpCDPK6 exhibited significant inhibitory effects on host cell invasion, while the immune sera of CpCDPK5 had no effects. These differences in protein localization, gene expressions, and neutralizing capacities indicated that the CpCDPK proteins may have different roles during the lifecycle of Cryptosporidium spp.